Traditional Marketing versus Online Marketing - Yusuf Mohammad, Anwar Yusuf Ali; Harun, Amran; Albert Gisip, Imelda (Penerbit UTHM, 2020)
In the current complex and competitive market, companies lose credibility and it is very easy to very difficult (Geraghty & Conway, 2016). Within the company oriented towards the rapid changes in the market such as competitors, distribution system, mass media, new technologies, customers' interests and tastes and expectations, in reality they do not gain the necessary knowledge to cope with this dynamic changes in the marketplace. To solve the problems, marketers may rely on traditional marketing which has a long history, it is a well-researched, long established, and proven method of getting product message out to the customer (Conway, 2016). This traditional marketing includes pretty much all advertising before the internet came along.